NEWBORN TREATED WITH CONTINUOUS RENAL REPLACEMENT THERAPY FOR CITRULINEMIA-TYPE 1 - Tosun, Demet; Akçay , Nihal; Menentoğlu , Mehmet; Şevketoğlu , Esra; Salihoğlu , Özgül (Sanamed, 2022)
Introduction: Hyperammonemia occurs as a result of the inability to convert ammonia, a metabolic toxin, into urea due to a block in the urea cycle, and there resulting neurotoxicity is responsible for the pathogenesis. Case Presentation: Our patient was 7 days old when followed up in an external center for 3 days with a preliminary diagnosis of neonatal sepsis. Lethargy, vomiting, tachypnea, and convulsions, which are frequently seen in the first neonatal forms of urea cycle disorders, were also present in our patient. He was referred to us as a result of high ammonia levels when he was examined in terms of congenital metabolic diseases. He was intubated due to the rapid development of respiratory failure. When he was admitted to our intensive care unit with hyperammonemia, light reflex could not be obtained, and widespread cutis marmaratus was developed. Continuous renal replacement therapy was started in our patient and administered intermittently for 120 hours. The glucose infusion rate was followed by high fluid. When it orally tolerated, it is supported with sodium benzoate and sodium stearyl fumarate to reduce ammonia. Nutrition was limited to protein with Basic P. Conclusion: After staying in the intensive care unit for 30 days, our patient was discharged with the recommendation of outpatient follow-up by the pediatric metabolism physician. When our patient came for his check up after two months,there was no nystagmus and no seizures.